Effects of Aflatoxin Exposure on Child Growth in the City of Karachi, Pakistan - Raza, Rashid; Ajaz, Aqsa (Journal of Research (Science), 2025)
Aflatoxins excreted in lactating human, in the form of aflatoxin M1 (AFM1) are carcinogenic substances. These are metabolites of aflatoxin B produced by fungi, Aspergillus flavusand Aspergillu sparasiticus. The current study was based on the aflatoxin exposure to the infants through breastmilk feeding. Human breast milk samples of 62 mothers through two hospitals were included in the study for the evaluation of AFM1. Standard HPLC method of analysis was used for analysis. A total of 21 samples out of 62 were found to contain AFM1. In the present study, the mean concentration of AFM1 in human breast milk (50 to 96pg/ L) has been found lower than the maximum acceptable limit (0.05mgkg-1) set by the European Union. The effects of aflatoxin contamination in breast milk on the growth of infants was assessed by maintaining anthropometric analysis of infants at 3, 6, 9 and 12months age. It has been observed that the aflatoxin contamination in the breast milk is significantly associated with infants impaired growth. The observed levels of aflatoxin in human breast milk was found to be associated significantly with weight, length, MUAC and head circumference deficit in the infants. The results confirming effect of chronic aflatoxin exposure to the growing infants and can be related with the impaired growth.